The Role Of The Produsen Pemulung Berdaya Cooperative In Improving The Economy Of Scavengers In Setu District, South Tangerang - Muhtadi Muhtadi Muhtadi; Muhammad Zahran Al Ariq (Empower : Jurnal Pengembangan Masyarakat Islam, 2024)
This research is motivated by the high poverty rate among the scavenger community in Setu District. This research aims to find out the role and results of empowering the waste picker community in improving their economy carried out by the South Tangerang Empowered Waste Picker Producer Cooperative. The research methodology used is a qualitative approach with descriptive analysis, data collection through observation, interviews, and documentation. The technique of collecting informant data using purposive sampling technique, with data analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results showed that in empowering the scavenger community through plastic bottle waste recycling activities in accordance with the theory of Jim Ife and Frank Tesoriero, namely the role of facilitation (social spirit, motivation, negotiation and mediation, building agreements, organizing, group facilitation), the role of educating (building awareness, providing information and training), the role of representation (obtaining sources, sharing knowledge and experience, cooperation and use of media), and technical roles (use of computer technology, presentation of reports and finance).  And the empowerment results obtained are in accordance with the theory put forward by Suharto, namely that cooperative members are able to meet their basic needs with a fixed income after becoming cooperative members and access to knowledge and skills.